Methods of Using Games in Teaching Grammar - Babaeva Gulzira Sarsenbaevna (International Journal on Integrated Education, 2022)
This article deals with the methodology of teaching foreign languages. The article briefly describes the techniques that have a teaching and developing character in the formation of grammatical skills, expanding the horizons of students.